Blood counts in extremely low birthweight infants. Issue 1 (January 1988) - McIntosh, N; Kempson, C; Tyler, R M
Abstract : White blood, neutrophil, and platelet counts were higher in 101 infants with appropriate weight for gestational age than in 42 infants who were small for gestational age. The recognised postnatal rise in counts was seen in the infants of appropriate weight, but in the infants who were small for gestational age the counts fell for the first three days.